Soil Degradation and Prospects for Their Restoration in Ba-Illi (Chari-Baguirmi) in the Sahelo-Sudanian Zone of Chad - Issiné, Agoubli; Guiguindimbaye, Madjimbé; Ngarkoudoum, Ngarhornadji; Téguinet, Biaksoubo; Touroumgaye, Goalbaye (International Journal of Applied Sciences and Biotechnology, 2026)
A study conducted in the sub-prefecture of Bâ-Illi, located in southern Chad, aimed to assess the state of agricultural soil degradation and explore prospects for its restoration. A survey was carried out among producers and other stakeholders involved in agricultural activities. The study reveals that the primary method of land acquisition is inheritance, followed by leasing. Producers are aware that declining field yields result from soil degradation caused by inadequate farming techniques. They employ a variety of techniques, ranging from no-till farming and mulching to half-moon planting.